Ammonium Pertechnetate in Mixtures of Trifluoromethanesulfonic Acid and Trifluoromethanesulfonic Anhydride. Issue 3 (3rd December 2021) - Zegke, Markus; Grödler, Dennis; Roca Jungfer, Maximilian; Haseloer, Alexander; Kreuter, Meike; Neudörfl, Jörg M.; Sittel, Thomas; James, Christopher M.; Rothe, Jörg; Altmaier, Marcus; Klein, Axel; Breugst, Martin; et al.
Abstract: Ammonium pertechnetate reacts in mixtures of trifluoromethanesulfonic anhydride and trifluoromethanesulfonic acid under final formation of ammonium pentakis(trifluoromethanesulfonato)oxidotechnetate(V), (NH4 )2 [TcO(OTf)5 ]. The reaction proceeds only at exact concentrations and under the exclusion of air and moisture via pertechnetyl trifluoromethanesulfonate, [TcO3 (OTf)], and intermediate Tc VI species. 99 Tc nuclear magnetic resonance (NMR) has been used to study the Tc VII compound and electron paramagnetic resonance (EPR), 99 Tc NMR and X‐ray absorption near‐edge structure (XANES) experiments indicate the presence of the reduced technetium species. In moist air, (NH4 )2 [TcO(OTf)5 ] slowly hydrolyses under formation of the tetrameric oxidotechnetate(V) (NH4 )4 [TcO(TcO4 )4 4 ] ⋅10 H2 O. Single‐crystal X‐ray crystallography was used to determine the solid‐state structures. Additionally, UV/Vis absorption and IR spectra as well as quantum chemical calculations confirm the identity of the species. Abstract : Ammonium pertechnetate is reduced to a green technetium(V) complex when left in triflic acid, while yellow pertechnetyl triflate and a purple Tc VI species form as intermediates. In the presence of excess pertechnetate, the ammonium salt of a pertechnetato–oxotechnetate, can be isolated.